Oxidative Burst, Peroxidase Activity, and Lignin Content of Sclerotium rolfsii Infected Peanut Tissue - ENDANG PUDJIHARTATI; SATRIYAS ILYAS; SUDARSONO SUDARSONO (HAYATI Journal of Biosciences, 2006)
The objectives of this experiment were to analyse physiological responses, such as oxidative burst reaction, peroxidase activity, and lignin content of healthy and S. rolfsii-infected peanut tissues. Differences in physiological responses among 24 peanut genotypes were determined, the disease severity was calculated and used to group resistance of tested genotypes. The regressions among observed peroxidase activity, lignin content and disease severity were used to determine the possible mechanisms of S. rolfsii resistance in peanut. Peanut seeds were grown in polybag and the growing plants were inoculated at the crown, stem, and leaf tissues. Results of the experiment indicated that infection of S. rolfsii in peanut did not induce oxidative burst. However, infection of the pathogen resulted in increased peroxidase activity and lignin content in the infected tissues. Regression analysis between peroxidase activity and disease severity showed negative slopes, indicating the more resistance the genotype, the more peroxidase activity in the tissue. Regression analysis between lignin content and disease severity was not significant. Key words: hypersensitive response (HR), resistance mechanisms, Sclerotium stem rot, disease response, Arachis hypogaea